Etching of Art Deco buildings - Ayan Ghosh (2023)
Elevation drawings of Palm Court, Oval View, and Belvedere Court. The stretch of reclaimed land around Churchgate Station underwent planned development in the 1930s. As a result of strict regulations, Maharshi Karve Marg has a dense concentration of Art Deco buildings, all built at a uniform height and using common design idioms.